(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2010)
This article focuses on the utilisation of the learner portfolio in the learning area Social Sciences as an alternative, authentic assessment tool to demonstrate the performance, progress and growth of learners in relation to the expected learning outcomes. The purpose of the portfolio, namely to promote learning, is not disputed, but the question is whether this assessment tool is really being used to its best advantage, and if not, why not. An attempt is made in this article to shed light on the apparent under utilisation of learner portfolios. Although the use of portfolios is widely commended, the purpose of this assessment tool is not being realised in practice. This begs the question: why use a portfolio if it is not optimally utilised?